Design and Synthesis of Potent HIV‑1 Protease Inhibitors Containing Bicyclic Oxazolidinone Scaffold as the P2 Ligands: Structure–Activity Studies and Biological and X‑ray Structural Studies - Ghosh, Arun K; Williams, Jacqueline N; Ho, Rachel Y; Simpson, Hannah M; Hattori, Shin-ichiro; Hayashi, Hironori; Agniswamy, Johnson; Wang, Yuan-Fang; Weber, Irene T; Mitsuya, Hiroaki (Journal of medicinal chemistry, 2018)
We have designed, synthesized, and evaluated a new class of potent HIV-1 protease inhibitors with novel bicyclic oxazolidinone derivatives as the P2 ligand. We have developed an enantioselective synthesis of these bicyclic oxazolidinones utilizing a key o-iodoxybenzoic acid mediated cyclization. Several inhibitors displayed good to excellent activity toward HIV-1 protease and significant antiviral activity in MT-4 cells. Compound 4k has shown an enzyme K i of 40 pM and antiviral IC50 of 31 nM. Inhibitors 4k and 4l were evaluated against a panel of highly resistant multidrug-resistant HIV-1 variants, and their fold-changes in antiviral activity were similar to those observed with darunavir. Additionally, two X-ray crystal structures of the related inhibitors 4a and 4e bound to HIV-1 protease were determined at 1.22 and 1.30 Å resolution, respectively, and revealed important interactions in the active site that have not yet been explored.